Hubungan dukungan teman sebaya dengan kesiapan anak usia sekolah menghadapi menarche - Cahyaningrum, Mutiara Putri; Warsiti, Warsiti; Anisa, Diah Nur (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Menarche is the first menstruation that marks the onset of puberty in girls and often causes anxiety if not accompanied by adequate preparedness. Unpreparedness in facing menarche can lead to anxiety, fear, negative perceptions of menstruation, and difficulties in coping with physical and emotional changes during puberty. Purpose: This study aims to determine the relationship between peer support and the readiness of school-aged children. Methods: This research used a quantitative design with a correlation analysis method and a cross-sectional approach. The sample consisted of 53 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed using the contingency coefficient correlation test. Results: The majority of peer support has good support, namely 36 respondents (67.9%), and for readiness, the majority of readiness is good, as many as 37 female students (69.8%). The results of the Fisher's Exact Test analysis obtained a p-value = 0.001 < 0.05, this indicates that there is a significant relationship between peer support and the readiness of school-age children to face menarche. The correlation coefficient value is 0.437, which indicates the closeness of the relationship in the moderate category. Conclusion: There is a significant relationship between peer support and the readiness of school-aged children to face menarche with a moderate strength of association.   Keywords: Menarche Readiness; Peer Support; School-Aged Children.   Pendahuluan: Menarche merupakan menstruasi pertama yang menandai awal pubertas pada anak perempuan dan sering kali menimbulkan kecemasan apabila tidak disertai kesiapan yang memadai. Ketidaksiapan dalam menghadapi menarche dapat menimbulkan kecemasan, ketakutan, persepsi negatif terhadap menstruasi, serta kesulitan dalam menghadapi perubahan fisik dan emosional pada masa pubertas. Tujuan: Untuk mengetahui hubungan dukungan teman sebaya dengan kesiapan anak usia sekolah menghadapi menarche. Metode: Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan metode correlation analysis, dan pendekatan waktu yang digunakan adalah cross-sectional. Sampel diambil dengan Teknik purposive sampling sebanyak 53 responden. Instrumen penelitian menggunakan kuesioner dan di analisis menggunakan uji korelasi koefisien kontingensi. Hasil: Dukungan teman sebaya mayoritas memiliki dukungan baik yaitu 36 responden (67.9%)  dan untuk kesiapan mayoritas kesiapan baik sebanyak 37 siswi (69.8%). Hasil analisis Fisher's Exact Test didapatkan hasil nilai p (value) = 0.001 < 0.05, maka hal ini menunjukan bahwa terdapat hubungan yang signifikan antara dukungan teman sebaya dengan kesiapan anak usia sekolah menghadapi menarche. Nilai koefisien korelasi sebesar 0.437, yang menunjukkan keeratan hubungan dalam kategori sedang. Simpulan: Terdapat hubungan yang signifikan antara dukungan teman sebaya dengan kesiapan anak usia sekolah menghadapi menarche dengan keeratan hubungan dalam kategori sedang.   Kata Kunci: Anak Usia Sekolah; Dukungan Teman Sebaya; Kesiapan Menarche.